Flexible Working Arrangements and Their Impact on Employee Engagement and Productivity (Maneggio, 2026)
Changes in the work landscape due to technological developments and modern organizational dynamics have encouraged the adoption of Flexible Working Arrangements as a human resource management strategy. This study aims to analyze the implementation of Flexible Working Arrangements and their impact on employee engagement and productivity. A qualitative approach with a case study design was used to gain an in-depth understanding of the experiences, perceptions, and meanings constructed by employees and management. Data collection was conducted through in-depth interviews, non-participatory observation, and documentation studies in organizations that have implemented flexible work practices on an ongoing basis. Data analysis was conducted thematically to identify patterns and relationships between phenomena. The results indicate that Flexible Working Arrangements encourage a paradigm shift from attendance-based supervision to results-based performance assessment. Work flexibility contributes positively to employee engagement by increasing autonomy, trust, and psychological well-being, although engagement levels are not uniform across all employees. Employee productivity tends to increase, particularly in jobs that require independence, time efficiency, and individual focus, while coordination challenges remain in teamwork. These findings confirm that Flexible Working Arrangements function optimally when integrated with adaptive leadership, a clear evaluation system, and consistent organizational support. This study provides theoretical and practical contributions to the development of sustainable flexible work policies